Promoting Anti-Bullying Behavior in Elementary Schools Through Storybooks Based on Living Values Education - Aulizha Suciatiningrum Inggaswana; Maelina Maelina; Najma Dhiya Ulhaq; Endang Herawan; Auliya Aenul Hayati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Bullying among elementary school students remains a significant issue that hampers social and emotional development. This study investigates the effectiveness of a picture storybook titled “Masalah Rambut”, developed based on the Living Values Education (LVE) approach, in promoting anti-bullying behavior and enhancing civic competence among young learners. A quasi-experimental design with a non-equivalent control group was employed. Participants were 68 third-grade students from SDN Ciremai Giri, Cirebon, divided equally into experimental and control groups. The experimental group received learning using the storybook and role-play activities, while the control group followed conventional instruction. Data were collected through pre-tests and post-tests on civic knowledge, civic skills, and civic disposition. Statistical analysis included paired t-tests and Cohen’s d to assess effectiveness. The experimental group showed significant improvements in civic competence, with p-values 0.001 across all dimensions. Effect size analysis indicated very large impacts: civic knowledge (d = 1.91), civic skills (d = 2.08), and civic disposition (d = 2.26). These gains outperformed those of the control group. Findings suggest that integrating LVE-based storybooks with interactive methods like role-play is highly effective in instilling empathy, tolerance, and responsibility. The emotional engagement offered by narratives and experiential learning fosters deeper internalization of anti-bullying values. Storybooks rooted in LVE present a promising pedagogical tool for character and citizenship education at the elementary level. Further research is needed to examine long-term impacts and broader applicability.